BNT162b2 mRNA COVID-19 vaccination in immunocompromised patients: A prospective cohort study. (November 2021) - Rahav, Galia; Lustig, Yaniv; Lavee, Jacob; Ohad Benjamini,; Magen, Hila; Hod, Tammy; Noga Shem-Tov,; Shmueli, Einat Shacham; Drorit Merkel,; Ben-Ari, Ziv; Halperin, Rebecca; Indenbaum, Victoria; et al.
Abstract: Background: Trials of the Pfizer-BioNTech BNT162b2 mRNA vaccine showed 95% efficacy in preventing symptomatic disease; however, the trials excluded immunocompromised patients (ICPs). We aim at analyzing antibody response in ICPs. Methods: A prospective cohort study was conducted at Sheba Medical Center, Israel, between January and April 2020, in 1274 participants who received the vaccine, including 1002 ICPs and 272 immunocompetent healthcare workers (HCWs). Antibodies were measured two-four weeks after vaccination by SARS-CoV-2 anti–receptor binding domain IgG antibodies (RBD IgG) and pseudo-virus neutralization assays. Multivariable logistic regression analyses were used to identify factors associated with vaccine-induced antibody response. Adverse events (AEs) were monitored. Findings: RBD-IgG antibodies were detected in 154/156 (98.7%) of patients with HIV, 75/90 (83.3%) with solid malignancies, 149/187 (79.7%) with myeloma, 83/111 (74.8%) following hematopoietic stem cell transplants, 25/36 (69.4%) following liver transplantation, 26/43 (60.5%) with myelodysplastic syndrome, 96/188 (51.0%) with chronic lymphocytic leukemia/non-Hodgkin's lymphoma, 50/110 (45.5%) following kidney transplantation, 15/80 (18.8%) following heart transplantation, and 269/272 (98.9%) in controls. There was a significant correlation r  = 0.74 (95%CI 0.69, 0.78) between RBD-binding IgG and neutralizing antibodies in all groups. Multivariate logistic regression analysis showed that age > 65 years (OR 0.41, 95%CI 0.30, 0.57) and underlying immunosuppression (OR 0.02, 95%CI 0.01, 0.07) were significantly associated with a non-reactive response of IgG antibodies. HIV patients showed a similar immunological response as healthy adults. The vaccine was safe without any episodes of rejection, graft-versus-host disease (GVHD) or allergy. Immunocompetent HCWs experienced significantly more AEs than ICPs. Interpretation: Antibody response to the Pfizer-BioNTech vaccine was highly variable among different ICPs; thus, individual recommendations should be provided for the different immunosuppression states. Funding: None.